History Learning Innovation: Khulafaur Rasyidin Interactive Media for Madrasah Tsanawiyah Students - Rahmawati, Rahmawati; Thaha, Hisban; Arifuddin, Arifuddin; Susanti, Irna (South Sulawesi Education Development (SSED), 2024)
This article discusses the development of Islamic Cultural History learning media for Khulafaur Rasyidin grade VII MTsN 1 Tana Toraja based on Box and Q.R. Code Quiz Paper. This study aims to determine the media's validity, practicality, and effectiveness. Using the Research and Development (R&D) method with the Plom model, the research was conducted on grade VII students at MTsN 1 Tana Toraja. Data were collected through questionnaires, interviews, and tests and analyzed in a quantitative descriptive manner. The results showed that this Media was valid, with a percentage of 90% by media experts, 100% by material experts, 87.9% by linguists, and 100% by Islamic Cultural History teachers. The practicality of this media reached 87.9%, and its effectiveness was shown by a post-test score with a sig (2-tailed) of 0.024 < 0.05, indicating that this Media was effectively used in teaching. The results of this study confirm that the Media Based on Box and Q.R. Code Quiz Paper is a valid, practical, and effective learning tool for teaching Islamic Cultural History.